Vitamin D in Multiple Sclerosis—Lessons From Animal Studies - Haindl, Michaela Tanja; Hochmeister, Sonja (Frontiers in Neurology, 2021)
Multiple Sclerosis is a multifactorial disease of the central nervous system with both genetic and environmental causes. The exact disease mechanisms are still unclear. Consequently, research of possible treatment and preventive measures cover a large setting of heterogeneous approaches. Vitamin D is one of these approaches and in many trials the relation of Vitamin D serum levels and Multiple Sclerosis disease risk and activity describe different effects with sometimes inconsistent findings. Animal models are substantial for the research of disease mechanisms and many of the drugs that are currently in use in Multiple Sclerosis have been developed, tested or validated via animal studies. Especially when clinical studies show contradicting findings, the use of standardized settings and information about the mechanistic background is necessary. For this purpose, animal models are an essential tool. There is a variety of different experimental settings and types of animal models available, each of them with own strengths but also weaknesses. This Mini-Review aims to overview results of Vitamin D studies in different animal models and sums up the most important recent findings.